2014
DOI: 10.1021/ja5014745
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Polymerization of a Strained [3]Nickelocenophane: A Route to Polynickelocenes, a Class of S = 1 Metallopolymers

Abstract: We report the synthesis, reactivity studies, and ring-opening polymerization of a tricarba[3]nickelocenophane. The resulting green polynickelocene (5) possesses a -(CH2)3- spacer between the nickelocene units and is shown to be of high molecular weight. SQUID magnetometry measurements indicate that 5 is a macromolecular material with an S = 1 repeat unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 63 publications
4
46
0
Order By: Relevance
“…Paramagnetic polynickelocene 7 was also found to exhibit significant antiferromagnetic spin-spin interactions, with evidence for intramolecular spinspin coupling along the polymer chains. 29 Herein we demonstrate that, as a consequence of the weaker Ni-Cp bonds (M-Cp dissociation energy is 250 kJ mol -1 for nickelocene vs. 305 kJ mol -1 for ferrocene), 31 polynickelocene 7 can exist in either a static or labile state, and in the latter case forms a dynamic equilibrium with monomer 5 and small amounts of cyclic oligomers 6x, under a range of conditions (Fig. 1d).…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Paramagnetic polynickelocene 7 was also found to exhibit significant antiferromagnetic spin-spin interactions, with evidence for intramolecular spinspin coupling along the polymer chains. 29 Herein we demonstrate that, as a consequence of the weaker Ni-Cp bonds (M-Cp dissociation energy is 250 kJ mol -1 for nickelocene vs. 305 kJ mol -1 for ferrocene), 31 polynickelocene 7 can exist in either a static or labile state, and in the latter case forms a dynamic equilibrium with monomer 5 and small amounts of cyclic oligomers 6x, under a range of conditions (Fig. 1d).…”
Section: Introductionmentioning
confidence: 62%
“…The β protons of monomer 5 were observed at -29.0 ppm (α protons are not observed, as reported previously). 29 Integration of the shifts corresponding to Cp protons at high field after 24 h indicated that ca. 69% of the [3] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Thus, analogues of PFS with other elements in the bridge or containing different metals to iron (in some cases in combination with alternative π-hydrocarbon ligands) have been prepared and their ROP has been successfully demonstrated in a growing number of cases. This provides a route to new and fascinating metallopolymers with modified properties, 222,[399][400][401][402][403][404][405] and studies of these materials are likely to constitute a broad new area of future research.…”
Section: Summary and Future Workmentioning
confidence: 99%